Heat Stress-Dependent Association of Membrane Trafficking Proteins With mRNPs Is Selective - Wolff, Heike; Jakoby, Marc; Stephan, Lisa; Koebke, Eva; Hülskamp, Martin (Frontiers in Plant Science, 2021)
The Arabidopsis AAA ATPase SKD1 is essential for ESCRT-dependent endosomal sorting by mediating the disassembly of the ESCRTIII complex in an ATP-dependent manner. In this study, we show that SKD1 localizes to messenger ribonucleoprotein complexes upon heat stress. Consistent with this, the interactome of SKD1 revealed differential interactions under normal and stress conditions and included membrane transport proteins as well as proteins associated with RNA metabolism. Localization studies with selected interactome proteins revealed that not only RNA associated proteins but also several ESCRTIII and membrane trafficking proteins were recruited to messenger ribonucleoprotein granules after heat stress.